Farm Households Livelihood Diversification and Poverty Alleviation in Giwa Local Government Area of Kaduna State, Nigeria - Oyinbo, Oyakhilomen; Tobi Olaleye, Kehinde (Consilience, 2016)
This study was undertaken to determine the effect of livelihood diversification on poverty alleviation in Giwa Local Government Area of Kaduna state, Nigeria. The study utilized primary data collected through a questionnaire administered to 100 respondents selected using purposive and random sampling procedure. Data were analyzed using simple descriptive statistics, the FGT poverty model and Tobit regression model. The result of FGT poverty model revealed that the incidence of poverty among the farming households was 30%, and this implies that 70% of the farm households were non-poor. The result of the Tobit regression showed that livelihood diversification was significant at 1% probability level and was negatively related to the poverty level of the farmers. This implies that a farming household head who engages in a number of livelihood activities has a lower likelihood of being poor. This is on the premise that increase in the number of livelihood activities increases the income of the farmers and invariably their purchasing power and welfare. It is recommended that awareness and skills acquisition training programmes should be established at the grass root by the local government authority to ensure that farmers are not only practising farming as their only means of livelihood but also a wide range of income generating activities to improve their well being.